Identification of Bond-Slip Behavior of GFRP-ECC Using Smart Aggregate Transducers - Zhang, Lifei; Zheng, Yu; Hu, Shaowei; Yang, Jiasheng; Xia, Lipeng (Frontiers in Materials, 2020)
The bond behaviour of Engineering Cementitious Composites (ECC) and Glass Fiber Reinforced Polymer (GFRP) bar has a strong effect on the behaviour of this composite structure significantly. However, it is difficult to detect the failure mode and damage status of the interface using traditional test methods. It is also due to the ECC mechanical behaviour of strain-hardening. As a result, an effective monitoring method using a patch lead zirconate titanate (PZT) transducers and an active sensing technology was proposed to detect the internal damage. In this active sensing technology, a PZT smart aggregate was bonded on the middle surface of ECC acting as a sensor. This paper conducted a series of experimental studies on the bond behaviour of GFRP reinforced ECC based on pull-out test. The test results were presented and discussed to investigate the bond-slip relationship and failure mechanism between FRP reinforcing bars and ECC matrix. The interfacial damage status between ECC and GFRP can be represented by the attenuation change of the stress wave. Finally, a damage index (DI) using the wavelet packet analysis was proposed to evaluate and quantify the FRP-ECC interaction damage level. The analytical results reveal that the debonding and failure mechanism can be detected by using this DI index values and the influence of the diameter of reinforcing bars should be considered with the Poisson’s effect.